Pengaruh Lingkungan Kerja dan Upah Karyawan terhadap Produktivitas Kerja Karyawan Pada PT. Indah Logistik Cargo Cabang Pematangsiantar - Sinambela, Rismawi Apriani; Sibagariang, Susy Alestriani; Meyana Sitorus, Debbi Petra (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This study aims to analyze the effect of the talking stick learning model and achievement motivation on social studies learning outcomes for class VIII students. This research method uses the experimental method. Data collection techniques using tests, questionnaires, and documentation. A sample of 64 respondents was taken from a total population of 351 students of SMP Negeri 1 Pematang Siantar. The data analysis technique used normality test, hypothesis testing with multiple linear regression analysis and t test and F test. The results showed that the talking stick learning model and achievement motivation had a positive and significant influence on students' social studies learning outcomes.